Evaluation of Self-Compacting Concrete Strength with Non-Destructive Tests for Concrete Structures - Nepomuceno, Miguel (2020)
Submitted by Miguel Costa Santos Nepomuceno (mcsn@ubi.pt) on 2020-01-21T23:14:54Z No. of bitstreams: 1 MN,LB- Comparison of NDT for NVC and SCC, Appl.Sci. 2019, 9(23),5109, 2019.pdf: 6352807 bytes, checksum: 6d4e68525342035aa406faaff59ea1fb (MD5)